Cloth seals : an illustrated reference guide to the identification of lead seals attached to cloth : from the British perspective - Elton, Stuart F., (Archaeopress archaeology., 2017)
This text is intended to be a repository of the salient information currently available on the identification of cloth seals, and a source of new material that extends our understanding of these important indicators of post medieval and early modern industry and trade.